Attitudes of Primary School Teachers Toward Inclusive Education - Radojlovic, Jasmina; Kilibarda, Tatjana; Radevic, Svetlana; Maricic, Milena; Parezanovic Ilic, Katarina; Djordjic, Milan; Colovic, Sofija; Radmanovic, Branimir; Sekulic, Marija; Djordjevic, Ognjen; Niciforovic, Jovan; Simic Vukomanovic, Ivana; et al. (Frontiers in Psychology, 2022)
Background: Our study will address the attitudes of primary school teachers towards inclusive education. Methods: The research is the cross-sectional study type. It targeted the population of teachers of lower primary schools and was conducted in three primary schools on the territory of Belgrade, Serbia in 2021. The sample included 64 primary school teachers in the lower grades of primary school (grades 1-4). As a research instrument, it was used The Questionnaire for Teachers, which is part of the project "Education for the Knowledge Society" of the Institute for Pedagogical Research in Belgrade. Dependent variables measured in the study referred to the attitudes of primary school teachers towards inclusive education. Category variables are presented as frequencies and the Chi-square (χ2) test was used to compare differences in the frequency of these variables. Results: One in three teachers 32.8% thought that inclusion was useful for children with disabilities, 29.7% of them thought that schools did not have the conditions for inclusive education, while one in four teachers 25% that inclusion is not good. Observed by gender, age, and length of service, the attitudes of professors did not show a statistically significant difference. Conclusion: Investing more resources and time in developing and implementing special education policies can promote successful inclusive education.